Short-term measurements of indoor environmental quality in selected offices – case study - Meciarova, Ludmila; Vilcekova, Silvia; Kridlova Burdova, Eva; Zoran Apostoloski, Ilija; Kosicanova, Danica (International Conference “Environmental Engineering”, 2017)
Decent quality of indoor air is important for health and wellbeing of building users. We live, work and study in indoors of various types of buildings. Often people are exposed to pollutants at higher concentrations than these that occur outdoors. Continual investigation of indoor air quality is needed for ensuring comfort and healthy environment. Measuring and analysis of occurrence of physical, chemical and biological factors is the first step for suggestion of optimization measures. Inside school buildings there are often inadequate indoor climate conditions such as thermal comfort parameters or ventilation. The aim of this study was determination of indoor environmental quality in selected offices in the building of elementary school in Slovakia. The values of operative temperature were not within the optimum range of values for the warm period of the year in one of the monitored offices. The intensity of illumination was lower in the two offices. Low levels of particulate matters were measured except the one office where permissible value was exceeded by 7.6%.